3(m-z)+5(2m-z)=0

Simple and best practice solution for 3(m-z)+5(2m-z)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(m-z)+5(2m-z)=0 equation:


Simplifying
3(m + -1z) + 5(2m + -1z) = 0
(m * 3 + -1z * 3) + 5(2m + -1z) = 0
(3m + -3z) + 5(2m + -1z) = 0
3m + -3z + (2m * 5 + -1z * 5) = 0
3m + -3z + (10m + -5z) = 0

Reorder the terms:
3m + 10m + -3z + -5z = 0

Combine like terms: 3m + 10m = 13m
13m + -3z + -5z = 0

Combine like terms: -3z + -5z = -8z
13m + -8z = 0

Solving
13m + -8z = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '8z' to each side of the equation.
13m + -8z + 8z = 0 + 8z

Combine like terms: -8z + 8z = 0
13m + 0 = 0 + 8z
13m = 0 + 8z
Remove the zero:
13m = 8z

Divide each side by '13'.
m = 0.6153846154z

Simplifying
m = 0.6153846154z

See similar equations:

| 7p^2=-18p-8 | | 12x+15(312-x)=13*312 | | 33x^2+39x=0 | | -86=-2(3n+1)-6n | | -83=10x+97 | | 7y+(5y+5)= | | 8x+5-6(x+1)=7x+3 | | 2y+3(y-9)=-3(3y-18)-y | | -7(1+3x)=161 | | 1=5p-2-2 | | (c)8-10=3c+5 | | 5-[2(-4)-1]=10-x | | 2x+20=46 | | -212=-2-6(5v-2) | | 3(4-7)=-21+12z | | 5-[(-4)-1]=10-x | | x^3+2x^3=72 | | v^2-16-6v=0 | | -4y-1(5y+6)=-7y+3 | | -2(8n+1)-4(n+5)=-2 | | 2/3(3x-9)=1/4(4x-12) | | 13r-8-12= | | 10x+5+8=12x-3x+8 | | 9=4x-x | | 6(1-2m)-4(m+1)=50 | | v=x(19-2x)(8.5-2x) | | 600=4x+8x | | 600=4x*8x | | -143=-11*x | | -6(5-7r)+4(-4r-5)=28 | | 15x-3-4x=21x-8-25 | | 4(x)-4(2x)=600 |

Equations solver categories